2018
DOI: 10.28991/esj-2018-01155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Abiotic Soil Parameters as a Factor in the Success of Invasive Plant Species

Abstract: Plant species dispersal has been strongly enhanced by human activities. Introduced species have to cope with indigenous species and local conditions. They may avoid indigenous species by occupying new (abiotic) territory. Once a species is established it may become a pest, and may seriously threaten other species and ecosystems.In this paper we focus on invasive plant species of the Dutch flora. We make two comparisons: (1) Dutch neophytes (i.e. arrived in The Netherlands after 1825) vs. indigenous Dutch flora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Common species also had no associations with any of the soil variables examined. This finding was surprising, as other studies have reported that common species may tolerate a broader range of environmental circumstances than rare species (Rabinowitz et al., 1979; Wamelink et al., 2014, 2018), such as greater ability to occupy habitats across various abiotic soil conditions (Wamelink et al., 2014). The absence of associations between species with soil properties may be attributed to the nutrient acquisition strategies of Australian native plants in our study system.…”
Section: Discussionmentioning
confidence: 84%
“…Common species also had no associations with any of the soil variables examined. This finding was surprising, as other studies have reported that common species may tolerate a broader range of environmental circumstances than rare species (Rabinowitz et al., 1979; Wamelink et al., 2014, 2018), such as greater ability to occupy habitats across various abiotic soil conditions (Wamelink et al., 2014). The absence of associations between species with soil properties may be attributed to the nutrient acquisition strategies of Australian native plants in our study system.…”
Section: Discussionmentioning
confidence: 84%
“…Plots that were georeferenced and below an altitude of 500 m were linked to an AAT (based on the year the plot was recorded and the four previous years). The AAT for each plot was linked with the species present at that location, which facilitated the estimation of an AAT response curve for each species using a Spline 22,23,28 . We de ned the range of the occurrence of each species as the annual temperature between the 5th and 95th percentiles of the response of the species.…”
Section: Methodsmentioning
confidence: 99%
“…The method used here follows that of Wamelink et al 22,23 , but with soil pH changed to AAT in the model. We combined two European databases to link the AAT with the vegetation plots and the species present.…”
Section: Methodsmentioning
confidence: 99%
“…The main approaches to the development and design of modern systems of local and remote monitoring of parameters of agricultural and technical facilities by means of modern sensor and microprocessor technologies using current research methods are presented in (Vu, 2011;Ahn et al, 2017;Changizian et al, 2017;Pash et al, 2017;Shirsath et al, 2017;Zade et al, 2017;Drapaca, 2018). For example, modern approaches to biological object modeling, such as mathematical modeling of engineering systems, in view of various destabilizing effects are presented in the paper (Drapaca, 2018); the main approaches to the environmental factors which are distributed in space and time, and affect the quality of technical systems are presented in the paper (Pash et al, 2017); the study (Changizian et al, 2017) focuses on the results of research on ensuring effective control of photoelectric signals in technical objects.…”
Section: Current Research Findingsmentioning
confidence: 99%
“…Currently, a wide range of scientific and technical research is devoted to the development of computerized technologies for the study of production processes in the agricultural segment of the national economies (Polat, 2017;Wamelink et al, 2018). The relevance of the research in this subject area is due to the high rates of research intensity of modern protected horticulture.…”
mentioning
confidence: 99%